The Extent to Which Teachers Employ Life Skills in Physical Education Classes from the Perspective of Educational Supervisors - Al-soud, Mahmoud Awad; Al-naimat, Mahmoud Mousa (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to identify the extent to which teachers employ life skills in the classes of physical education from the point of view of educational supervisors. It also examines the differences in the extent to which teachers employ life skills in the classes of physical education according to the variables of gender and region. Methods: The study employed a descriptive approach, aligning with its nature and objectives. A random sample of 53 supervisors was chosen. Data collection involved a 30-item measure gauging teachers' utilization of life skills in physical education lessons. A three-level rating scale (low 1-2.33, medium 2.34-3.67, high 3.68-5.00) was applied to interpret arithmetic means. Analysis utilized means, standard deviations, percentages, t-test, Cronbach's alpha, and one-way ANOVA. Results: The results showed that the extent to which teachers employ life skills in the physical education lesson from the point of view of educational supervisors has a moderate degree. The results showed that teachers encourage teamwork and promote positive behaviors among students. One of the findings of the study was that there were no statistically significant differences at the indicative level (α=0.05) attributable to gender variables and the region. Conclusion: The study recommends the need to hold educational courses for teachers to train them on how to provide learners with life skills during the classes of physical education, and to improve the performance and professional growth of the teacher of physical education.